Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


In this kind of equation you can just skip the square as it changes nothing here. It means that we can solve it like this: 

(y-2)^2=0 \\ y-2=0\\y=2

Ok, let's check if it adds up now: 

y=2 \\ (2-2)^2=0 \\ 4-4=0 \\ 0=0

1 2 1
(y-2)^{2} =0^{2} 
so y-2=0
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts